2015
DOI: 10.1093/jee/tov278
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spinosad Resistance on Transmission of Tomato Spotted Wilt Virus by the Western Flower Thrips (Thysanoptera: Thripidae)

Abstract: Tomato spotted wilt virus (TSWV) is transmitted by Frankliniella occidentalis (Pergande) in a persistent-propagative manner. We previously observed significant results in terms of feeding behavior of spinosad-susceptible (Ivf03) and -resistant (Spin-R) strains of F. occidentalis using electrical penetration graph. TSWV transmission by the two strains was compared in the present study. The results showed that the titer of TSWV-N RNA (a part of S RNA of TSWV and encoding the nucleocapsid protein) in Ivf03 and Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Although B. tabaci Q cannot transmit TSWV ( Zhao et al, 2015 ), we showed in this study that it can acquire and retain TSWV. In the interaction between TSWV, B. tabaci Q, and host plants, it follows that any effects of TSWV on B. tabaci Q are direct, i.e., do not result from the changes in the host plant that could occur following TSWV transmission.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Although B. tabaci Q cannot transmit TSWV ( Zhao et al, 2015 ), we showed in this study that it can acquire and retain TSWV. In the interaction between TSWV, B. tabaci Q, and host plants, it follows that any effects of TSWV on B. tabaci Q are direct, i.e., do not result from the changes in the host plant that could occur following TSWV transmission.…”
Section: Discussionmentioning
confidence: 58%
“…TSWV also can enhance the fitness of F. occidentalis ( Maris et al, 2004 ). Unlike TYLCV, TSWV is not transmitted by B. tabaci ( Zhao et al, 2015 ). Similarly, TYLCV is not transmitted by F. occidentalis .…”
Section: Introductionmentioning
confidence: 99%
“…WFT is the most common and efficient vector of tomato spotted wilt virus (TSWV), which can result in serious disease of hundreds of species of vegetables and ornamentals (Moyer, ; Reitz & Funderburk, ). In spite of TSWV being first isolated from peanut ( Arachis hypogaea ) in Guangdong province in 1984 (Z. Y. Xu, Zhang, & Chen, ), TSWV has rapidly spread in China following WFT's invasion and spread over the last 10 years (X. F. Cheng, Dong, & Fang, ; F. Li et al, ; Zhao et al, ). WFT fitness was elevated or at least maintained normal status, after feeding on TSWV‐infected host plants compared with healthier ones (Zhu, Zhang, & Lv, ).…”
Section: Invasion Biology and Ecologymentioning
confidence: 99%
“…WFT fitness was elevated or at least maintained normal status, after feeding on TSWV‐infected host plants compared with healthier ones (Zhu, Zhang, & Lv, ). Gender asymmetry was also observed as TSWV transmission rates of males were significantly higher than females (Zhao et al, ). This phenomenon could explain the differences in the feeding behavior between male and female WFT (Zhao et al, ).…”
Section: Invasion Biology and Ecologymentioning
confidence: 99%
See 1 more Smart Citation